Juventude @ e as Jornadas de junho: as manifesta????es de rua de 2013, em Imperatriz-MA - Menis, Paulo (2015)
Brazil has been a recurrent stage in popular mobilizations which leaves marks in its history. Among participants, leaders and organizers of these protests we can observe the university students. They are young people who do not have a clear definition of social class or they have social condition with an expiration date. The June Journeys, mobilizations that happened in June 2013, is part of this group of remarkable protests that as the same time were characterized as the first one to use Social Medias. The Social Medias speed, insertion, expansion and strength could aloud the young people, who participated in the protests, to show their dissatisfaction and to present their claims in a unison way, through 137 cities, 25 States and the Federal District, among them Imperatriz, a city in the State of Maranh??o. This work must analyze the way the young students in university education, who live in Imperatriz ??? MA and participated in the protests of June 2013, understood the acts in the background of June Journeys. In this research, which is mainly qualitative and exploratory, was used questionnaire and interviews previously structured, since pursued more specifically: to identify the social, economic, demographic and educational profile of the participants; to investigate the reasons that lead these young people to take part in the protests; to investigate if the young people availed themselves of the social Medias for the protests, and to verify how the participants understood the protests effects during their accomplishment, and their perspective for the future. During the analysis of the obtained data was used the content analysis with historical materialism, which allowed the description, intervention, and the interpretation of the information collected. The obtained results could attend to the proposed objectives: they showed the protests organization backstage, which had politicians??? fees, different from what was disclosed. They also had the participation of government officials and leaders; they evinced the importance of Social Medias, mainly the Facebook,and they showed the difference between the young people organized the protests, who belonged to upper middle class families, and the young participants, who belonged to humbler families. At the conclusion of the research, some recommendations are introduced in order to search for a major knowledge and comprehension of the current young university students